History of religions in Ukraine - Kolodnyj, Anatolij Mykolajovyč 1937- (1997)
VII International Round Table, held on May 12-14, 2007 on the basis of the Lviv Mykes), the clori rions of religions, like the previous ones, considered a broad aspect of the problems of religious science. Many scientists from Ukraine, near foreign countries came to Lviv. What prevailed in the thematic orientation of scientific reports and messages? First of all, this is an understanding of the creative work of not only well-known Ukrainian thinkers and theologians (G. Skovoroda, A. Sheptytsky, I. Ogienko, I.Potiy, etc.), but also new figures - A. Monastyrsky, S.Tomasashkovsky, Yu.Levinsky , K.Sokolovsky, T.Mostovoi, J.Zastirts and others. Again the attention of researchers was drawn to the history of Greek Catholicism, the Orthodox - autocephalous movement.
VII Міжнародний круглий стіл, який відбувся 12-14 травня ц.р. на базі Львівського Микесс)клорії релігій, як і попередні, розглянув широкий аспект проблем релігієзнавчої науки. До Львова приїхали багато науковців з України, близького зарубіжжя. Що переважало в тематичній зорієнтованості наукових доповідей і повідомлень? Насамперед це осмислення творчого доробку не лише широко відомих українських мислителів і богословів (Г.Сковороди, А.Шептицького, І.Огієнка, І.Потія та ін.), а й нових постатей - А.Монастирського, С.Томашківського, Ю.Левинського, К.Соколовського, Т.Мостового, Й.Застирця та ін. Знову привертала увагу дослідників історія греко-католицизму, православно - автокефального руху.